4D Biofabrication of T-Shaped Vascular Bifurcation - Kitana, Waseem; Apsite, Indra; Hazur, Jonas; Boccaccini, Aldo R.; Ionov, Leonid (Advanced Materials Technologies, 2022)
4D Biofabrication – a pioneering biofabrication technique – involves the automated fabrication of 3D constructs that are dynamic and show shape-transformation capability. Although current 4D biofabrication methods are highly promising for the fabrication of vascular elements such as tubes, the fabrication of tubular junctions is still highly challenging. Here, for the first time, a 4D biofabrication-based concept for the fabrication of a T-shaped vascular bifurcation using 3D printed shape-changing layers based on a mathematical model is reported. The formation of tubular structures with various diameters is achieved by precisely controlling the parameters (e.g. crosslinking time). Consequently, the 3D printed films show self-transformation into a T-junction upon immersion in water with a diameter of a few millimeters. Perfusion of the tubular T-junction with an aqueous medium simulating blood flow through vessels shows minimal leakages with a maximum flow velocity of 0.11 m s–1. Furthermore, human umbilical vein endothelial cells seeded on the inner surface of the plain T-junction show outstanding growth properties and excellent cell viability. The achieved diameters are comparable to the native blood vessels, which is still a challenge in 3D biofabrication. This approach paves the way for the fabrication of fully automatic self-actuated vascular bifurcations as vascular grafts.
CRIS-Team Scopus Importer:2022-10-21
Keywords: 3D printing; 4D biofabrication; ADA-Gel; blood vasculature; vascular bifurcation